English Learning in Mastering Vocabulary Using Song Lyrics in Foreign Language Development Institution (FLDI) Nurul Jadid Islamic Boarding School - Al Anis, Abdullah; Rosyidah, Siti; Wulandari, Suci (Universitas Nurul Jadid, 2021)
Vocabulary is one of the important language elements in mastering English which is a form of 4 language skills, namely reading, listening, writing and speaking. Most people learning languages, especially English, must use vocabulary properly and correctly both in writing and in writing which makes the way of speaking more accurate. FLDI is an institution that specializes in the field of language, namely Arabic and English. This institution stimulates and develops the interest of language enthusiasts, both Arabic and English, researchers will see the extent to which the vocabulary mastery process is trained, studied, and practiced in language skills at the FLDI in the Al-Hasyimiyah Pondok area. Nurul Jadid Islamic Boarding School. The research was carried out from 20 June to 20 August 2021. This research is qualitative research whose type of research is a case study research on the method of learning English vocabulary in the field. The method of collecting data in the field in this research is using test techniques (giving material tests), interviews, and observations. The subjects in this study were teachers and students of the Institute for Foreign Language Development (FLDI), which consisted of 2 teachers teaching vocabulary lessons (Vocabulary) and 20 students with different classes in Elementary (basic) classes.